Evaluación De Colmenas De Apis Mellifera Durante La Pasantía En La Granja San Pedro De La Universidad Antonio Nariño (2023)
In Colombia, strategies have been developed and implemented to guarantee the optimal conditions for pollinators, which are a fundamental axis to maintain the ecosystems and biodiversity of our environment, since they transport pollen from one flower to another guaranteeing the reproduction of plants and thanks to these processes we feed on their fruits (Claro, Medina, 2021).